Influence Of 7 Sunnah Improves Higher Order Thinking Skills Of Indonesian Students In Mathematics (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The quality of mathematics education in Indonesia is of great concern. This is proven based on the survey results conducted by international survey institutions such as PISA and TIMSS and national survey institutions such as ACTION. This conclusion is strengthened by the fact that the UN scores for junior high and high school levels have decreased. Improving the quality of mathematics education in Indonesia, especially among Muslims, research on the relationship of students' persistence in performing worship with their high-level thinking skills was conducted. The purpose of this research is to (1) Formulating the application of the 7 Sunnahs of the Prophet Muhammad S.A.W. in mathematics using Higher-Order Thinking Skills (HOTS). (2) Analyzing the effect of implementing the 7 Sunnahs of the Prophet Muhammad S.A.W. in improving students' higher-order thinking skills/HOTS. (3) Analyzing the practice of worship that is most influential in the implementation of the 7 Sunnahs that affect the higher-order thinking skill/HOTS.This study uses a quantitative approach with data collection techniques through in-depth interviews, surveys, questionnaires, and documentation. The data is processed and analyzed using a computer as a tool and using the SPSS 16 for Windows program to determine the correlation of existing data. The research resulted in (1) A model of implementing the 7 Sunnahs in mathematics learning. The lesson begins with reciting surah Al-Fatihah, praying to the prophet, praying before studying, reciting Asmaul Husna, and reciting short surah in the Quran and ends with the advice to motivate students to be persistent in carrying out worship. (2) The implementation of the 7 sunnah that has significant influences is tahajud pray while the achievement of the competition that has a significant influence are KMNR competition, OSN competition, and International competition (3) The implementation of the 7 Sunnah that has significant influences are congregational pray, Dhuha prays, almsgiving, reading the Qur'an, sunnah fasting and maintaining ablution. This study found that the spiritual activity approach influenced improving students' higher-order thinking skills in mathematics. This learning model can be used in various non-formal educational institutions with having the same vision. This learning model can also be applied in formal education after being adapted to the situation and conditions of the school.